A novel tree-based algorithm to discover seismic patterns in earthquake catalogs. (June 2018) - Florido, E.; Asencio–Cortés, G.; Aznarte, J.L.; Rubio-Escudero, C.; Martínez–Álvarez, F.
Abstract: A novel methodology is introduced in this research study to detect seismic precursors. Based on an existing approach, the new methodology searches for patterns in the historical data. Such patterns may contain statistical or soil dynamics information. It improves the original version in several aspects. First, new seismicity indicators have been used to characterize earthquakes. Second, a machine learning clustering algorithm has been applied in a very flexible way, thus allowing the discovery of new data groupings. Third, a novel search strategy is proposed in order to obtain non-overlapped patterns. And, fourth, arbitrary lengths of patterns are searched for, thus discovering long and short-term behaviors that may influence in the occurrence of medium-large earthquakes. The methodology has been applied to seven different datasets, from three different regions, namely the Iberian Peninsula, Chile and Japan. Reported results show a remarkable improvement with respect to the former version, in terms of all evaluated quality measures. In particular, the number of false positives has decreased and the positive predictive values increased, both of them in a very remarkable manner. Highlights: Discovery of precursory patterns for medium-large earthquakes in Chile, the Iberian Peninsula and Japan. Seismic parameters' ability to predict earthquakes is confirmed. General purpose methodology: can be applied to any other area. Accuracy rate above 70%.